Organisation of in-process inspection and control of the lamination process in carbon fibre composites manufacturing - Kujinga, Aram (Cranfield University, 2006)
The lamination process is the core in the manufacture of carbon fibre composites. This thesis is a detailed study of the manner in which in-process inspection can be organised so that process flaws that subsequently result in defects can be eliminated or minimised. The quality management system and the inspection methods in force at Lola are thus subjected to intensive scrutiny so as to identify opportunities for improvement. A review of relevant literature on quality management, continuous improvement, mistake-proofing and zero defect initiatives helped map out a methodology for the research. The literature has also looked at the human issues that influence quality and inspection methods. The approach to the study has been to establish quality performance in the past and at present, establish quality attitudes and evaluate inspection methods. Visual inspection is the widely used method of inspection within the industry and instrument aided methods are still an area for research. Ways in which defects may be prevented from occurring and analysing the defects when they occur so as to get to the root causes have been suggested. This study has highlighted the need to adhere to standard operating procedures which account for errors that are avoidable. Motivation and inspiration can only be cultivated into workers through recognition and rewards. Employee engagement is very crucial and workers need to be supported with focussed training and appropriate working aids. Recommendations have been made on involving workers right from the design stage through the manufacturing process right to the customer. Customer requirements will need to be executed with certainty and all necessary information deemed useful will must be input at the design stage. In-process inspection must take a holistic approach i.e. both horizontal and vertical inspection. A point worth noting is that visual inspection accounts for at least 80% of inspections carried out in the manufacture of carbon fibre composites.